Homoclinic Solutions for a Second-Order Nonperiodic Asymptotically Linear Hamiltonian Systems - Qiang Zheng (Abstract and Applied Analysis)
We establish a new existence result on homoclinic solutions for a second-order nonperiodic Hamiltonian systems. This homoclinic solution is obtained as a limit of solutions of a certain sequence of nil-boundary value problems which are obtained by the minimax methods. Some recent results in the literature are generalized and extended.